School Financial Management in Meeting Infrastructure Standards (Case Study at SMP Negeri 17 in Serang City) - Lilik Nur Kholidah; Shintawati Shintawati; Heni Yunilda Hasibuan; Encep Syarifudin; Cucu Atikah (EDUTEC : Journal of Education And Technology, 2023)
The purpose of this study was to analyze and understand the fulfillment of school financial management facilities and infrastructure standards at SMP Negeri 17 Kota Serang. This research uses a qualitative approach with case studies. The informants in this study consisted of school principals, deputy director of facilities and infrastructure (wakasek), treasurers of Education Unit Operational Assistance (BOSP), and school committees. Data collection techniques were carried out through interviews, observation and documentation. Data analysis techniques use data reduction, data display and verification inference. Information accuracy is verified; credibility, transferability, reliability, and verifiability. The results of the study show that school financial management in meeting educational facilities and infrastructure standards for SMP Negeri 17 Serang City through planning and budgeting, administration and reporting and accountability according to Permendikbudristek 63 BOSP Juknis Year 2022. This study influences the importance of financial management to meet institutional and infrastructure standards education, because Stakeholders both internal and external can assess, analyze, monitor and fulfill various school needs.